Tuning lamella spacings for simultaneous strength-ductility improvements in heterogeneous lamella SiCp/2024Al composites - Kan Liu; Qifeng Cui; Lu Shi; Yunpeng Cai; Andong Hua; Yishi Su; Qiubao Ouyang; Di Zhang (Materials & Design)
Whether there is a limit in enhancing strength-ductility through refining heterogeneous lamella structures has garnered great attention for designing high-performance Al matrix composites. Here we investigated lamella spacing controlled strengthening-toughening behaviors in heterogeneous lamella micro- and nano-sized SiC particles (m- & n-SiCp)/2024Al composites. With increasing extrusion ratio, both thickness and grain size of fine grain (FG) bands were decreased while ultra-fine grain (UFG) dimensions were almost constant. Samples consisting of appropriately refined heterogeneous lamellas possess simultaneously enhanced strength and ductility: 632.5 MPa in yield strength, 757.1 MPa in ultimate tensile strength and 6.5 % in elongation, exhibiting a superior toughness of 42.8 MJ/m3 that is 58.5 % and 169.2 % higher than those of counterparts. Hetero-deformation induced (HDI) and dislocation strengthening as dominant mechanisms contribute more than 65 % to yield strength and intragranular n-SiCps compensate for the precipitation strengthening loss in UFG zones. High ductility benefits from both intrinsic and extrinsic toughening. The improved strain hardening capacity, achieved through synergy of extensive hetero-interfaces and dense long straight geometrically necessary dislocation (GND) arrays piled-up within FGs delays necking instability, while strain delocalization induced damage delocalization behavior inhibits premature fracture.